More Than Just Entertaiment How Does TikTok Empower Its User to Improve Their Speaking Skills - Sendi Suwantoro; Tintin Susilowati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
TikTok, as a short-video sharing platform, has experienced rapid growth among Gen Z, particularly in the context of education. This study aims to explore the potential of TikTok in enhancing English-speaking skills through storytelling. In this digital era, Gen Z tends to seek learning methods that are interactive, enjoyable, and relevant to their daily lives, and TikTok offers opportunities that align with these preferences. Various studies have shown that TikTok can help users improve their speaking skills, particularly through exposure to different accents, pronunciation, as well as opportunities to practice speaking in front of a camera and receive feedback from the community. The use of storytelling on TikTok provides students with the chance to practice speaking in various contexts in a creative and structured manner. This study adopts a literature review method to analyze previous findings regarding the use of TikTok in language learning. The conclusion of this study indicates that TikTok is not only an entertainment platform but also holds great potential as an effective tool for learning English, especially in honing speaking skills through storytelling. Therefore, educators need to leverage this technology to create more engaging and adaptive learning experiences in the Gen Z era